Strengthening Character and Discipline of Vocational High School Students at SMK Arung Samudera Banjarmasin Through Cadetship Approach - Kamsariaty Kamsariaty (Siber Nusantara of Community Service Review, 2025)
Vocational education plays a strategic role in producing work-ready graduates, where success is heavily influenced by soft skills mastery such as character and discipline. This community service research aims to strengthen the character and discipline of students at SMK Arung Samudera Banjarmasin through a Ketarunaan (semi-military) approach to address challenges in the maritime industry sector. The implementation method consists of four main stages: preparation (survey and module compilation), implementation (physical training/PT, mental coaching, and outbound), evaluation (pre-test and post-test), and sustainability through the formulation of Ketarunaan SOP. The results show a significant positive impact both quantitatively and qualitatively. Quantitatively, there was an average increase in student discipline scores of 20%, covering indicators of punctuality, neatness, and compliance with instructions. Qualitatively, the program successfully formed resilient mentalities, team spirit (korsa), and student leadership abilities. Additionally, student understanding of national insight and ethics reached scores above 85%. The conclusion is that the Ketarunaan approach is effective in bridging the gap between academic ability and maritime industry professionalism, and has been integrated into the school culture through permanent SOPs to guarantee program sustainability.